2018
DOI: 10.1016/j.optlastec.2017.09.040
|View full text |Cite
|
Sign up to set email alerts
|

Improve the material absorption of light and enhance the laser tube bending process utilizing laser softening heat treatment

Abstract: Laser forming is a flexible control process that has a wide spectrum of applications; particularly, laser tube bending. It offers the perfect solution for many industrial fields, such as aerospace, engines, heat exchangers, and air conditioners. A high power pulsed Nd-YAG laser with a maximum average power of 300 W emitting at 1064 nm and fiber-coupled is used to irradiate stainless steel 304 (SS304) tubes of 12.7 mm diameter, 0.6 mm thickness and 70 mm length. Moreover, a motorized rotation stage with a compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The ONCBA was defined as the external angle formed by the optic nerve in the optic canal and the optic nerve in the intracranial subarachnoid space at the entrance of the optic canal. 18 also related to visual field defect. 1 We found that severe sagittal bending of the optic nerve at the left or right exit of the optic canal greatly affects the VIS, or total visual function.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The ONCBA was defined as the external angle formed by the optic nerve in the optic canal and the optic nerve in the intracranial subarachnoid space at the entrance of the optic canal. 18 also related to visual field defect. 1 We found that severe sagittal bending of the optic nerve at the left or right exit of the optic canal greatly affects the VIS, or total visual function.…”
Section: Discussionmentioning
confidence: 90%
“…2G and 3). 18 The optic nerve is fixed in the optic canal. 26 The optic nerve sometimes bends three-dimensionally at the exit of the optic canal in patients with sellar and suprasellar tumors.…”
Section: Mrimentioning
confidence: 99%
“…Figure 3 shows two samples of laser tube forming. Laser beam absorption can also be performed to improve the obtainable bending angle [57]. Different materials, such as carbon steel, stainless steel, and nickel tubes, can be formed and used in various industries such as aerospace industries, engines, heat exchangers, and air conditioners [54][55][56][57][58][59][60].…”
Section: Laser Tube Bendingmentioning
confidence: 99%
“…Laser beam absorption can also be performed to improve the obtainable bending angle [57]. Different materials, such as carbon steel, stainless steel, and nickel tubes, can be formed and used in various industries such as aerospace industries, engines, heat exchangers, and air conditioners [54][55][56][57][58][59][60]. Statistical tools, such as Particle Swarm Optimization (PSO), can predict the bending angle and compensation of springback [58].…”
Section: Laser Tube Bendingmentioning
confidence: 99%
“…Using the model proposed by Hao and Li [3], Imhan et al [4] experimentally and analytically examined the changes in material properties during the laser forming. In another study, they also improved the bending angle in laser tube forming by increasing the absorption coefficient and formability of the material using laser softening heat treatment [5].…”
Section: Introductionmentioning
confidence: 99%